Analysis of ultrasonographic measurements of inferior vena cava and abdominal aorta diameters in neonates - Zhang, H Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2024)
Objective: To analyze the ultrasonographic measurements of inferior vena cava (IVC) and abdominal aorta in healthy full-term neonates throughout the early postnatal period. Methods: Prospective observational study was conducted. A total of 132 healthy full-term neonates, who were born at the Kunshan First People's Hospital between May 1st and August 30th, 2023, were enrolled as the study subjects. Two-dimensional and M-mode ultrasonography were used to measure the maximum and minimum diameters of the IVC and abdominal aorta in the early postnatal period. The IVC collapsibility index, the ratio of maximum IVC diameter to abdominal aorta diameter, and the ratio of minimum IVC diameter to abdominal aorta diameter were calculated. These neonates were stratified by gender, birth mode, gestational age and birth weight (<3 000 or ≥3 000 g), and independent sample t-test or Kruskal-Wallis H test was used to compare the ultrasonography measurements by different groups. Results: Among the 132 neonates, 81 were males, with a gestational age of (39.2±1.0) weeks, and a birth weight of (3 326±409) g. There were no significant statistical differences in the the maximum and minimum diameters of the IVC and abdominal aorta assessed by both two-dimensional and M-modes between the first and second days (all P>0.05). Additionally, no statistical differences were observed in the ultrasonographic measurements among neonates of different sexes, birth modes, and gestational ages (all P>0.05); but there were statistically differences between the group with birth weight of <3 000 g and the group with birth weight of ≥3 000 g (all P<0.05). There were no statistically differences in IVC collapsibility index, the ratio of the maximum diameter of IVC to the diameter of abdominal aorta, and the ratio of the minimum diameter of IVC to the diameter of abdominal aorta between the group with birth weight of <3 000 g and the group with birth weight of≥3 000 g (all P>0.05). Conclusions: The diameters of the IVC and abdominal aorta in healthy full-term neonates during the early postnatal period are correlated with birth weight. The IVC collapsibility index and the ratio of IVC diameter to abdominal aorta diameter are unrelated to birth weight and can be used to assess newborn blood volume or right cardiac preload